Britain and Europe : a Political History Since 1918. - Crowson, N. J. (Taylor & Francis, 2010)
This title presents a comprehensive account of Britain's uneasy relationship with continental Europe from the end of the First World War to the twenty-first century. Crowson considers 'Europe' in its broadest sense and examines prewar history and the role of key political institutions such as the Council of Europe and the Western European Union as well as Britain's relations with the European Union (EU). Subjects covered include: European perspectives on Britain as well as the other way round; key theories on European integration; the changing nature of Britain's global role; issues of soverei.